2008
DOI: 10.1021/jp8077437
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Passivation of Silicon Nanowires with C1−C6 Alkyl Chains through Covalent Si−C Bonds

Abstract: We report on the functionalization of Si NWs with C 1 -C 6 alkyl chains using a versatile two step chlorination/ alkylation process. We show that Si NWs terminated with C 1 -C 6 molecules, through Si-C bonds, connect alkyl molecules to 50-100% of the Si atop sites and provide surface stability that depends on the chain length and molecular coverage, according to the following order: COur results indicate that the oxidation resistance of (C 1 -C 2 )-Si NWs is significantly higher than equivalent 2D Si(100) surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 30 publications
7
89
0
Order By: Relevance
“…The alkylation rate of the short alkyl chains (C 1 -C 6 ) 52 at alkylation processes <100 min was higher than those for long alkyl chains (C 8 -C 10 ). The times required to achieve 92 ( 3% of the saturation level of the various adsorption curves, Γ sat , together with the related C-Si/ Si2p ratios, are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The alkylation rate of the short alkyl chains (C 1 -C 6 ) 52 at alkylation processes <100 min was higher than those for long alkyl chains (C 8 -C 10 ). The times required to achieve 92 ( 3% of the saturation level of the various adsorption curves, Γ sat , together with the related C-Si/ Si2p ratios, are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 78%
“…ref 57. XPS scans for Si NWs were employed and compared to that of 2D Si(100). 52 To determine the position/shift of the peaks, we have considered two main approaches: (I) the center-tocenter distances were fixed at 1.10 ( 0.10 eV between the C-Si and the C-C emissions and at 2.60 ( 0.10 eV between the C-O and the C-Si emissions; and (II) the center-to-center distance allowed flowing, while the full width at half-maximum (fwhm) was identical in Si NW and 2D Si(100) samples. XPS scans for Si NWs showed similar fwhm's for a Si-C bond compared to that of 2D Si(100).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high sensitivity, low-power consumption, fast-response times, and the compatibility with conventional silicon technology and readout circuitry, have the potential to get SiNW FETs to give us simple signal transductions of disease breathprints, as well as being amenable to miniaturization and scalability. [45][46][47][48][49][50] Results and Discussion…”
Section: Analysis Of the Clinical Samples Showed That The Optimized Smentioning
confidence: 99%
“…The center-to-center difference between the C-Si peak and the -CH 2 -CH 2 peak was 1.1 eV, as also observed in a previous study on Si NWs from Bashouti and co-workers. [46] Interestingly, we found that the center-to-center difference between the -CF 2 -CH 2 and -CH 2 -CH 2 peak was 1.3 eV, whereas for planar Si surfaces 0.9 eV was found. Also, the C-F peaks observed for Si NWs occur consistently at slightly higher values than observations for flat Si (111) surfaces.…”
Section: Surface Characterization Of the Si Nwsmentioning
confidence: 75%